Pendampingan Posyandu Kenanga Melalui Peningkatan Literasi Kesehatan Ibu Balita sebagai Upaya Penurunan Stunting di Desa Meteseh, Kecamatan Boja, Kabupaten Kendal - Fitria Dewi Puspita Anggraini; Aprianti Aprianti; Vilda Ana Veria Setyawati; Nida Tahara Salsabila (Pusat Riset dan Inovasi Nasional, 2022)
Stunting is a national program that involves specific and sensitive interventions in it. Activities carried out by cadres are still limited to registering, weighing, measuring length/height, filling out KMS and distributing PMT. Infrastructure facilities at the Posyandu Kenanga are still very limited. The measurement of the body length of toddlers who cannot stand only uses a cloth meter. This will affect the measurement results in the process of monitoring the growth and development of children under five. The purpose of this service activity is to provide education about stunting to improve maternal health literacy and provision of posyandu infrastructure facilities in the form of nameplates and digital baby scales. As a result, from around 54 mothers of children under five who participated in posyandu activities, 24 of them were successfully assessed for pretest and posttest scores. There was an increase in the knowledge score from 73 to 79 with an average of 3,042 increasing to 3,291. The value of the Gain Score calculation shows that the average value of N Gain Score for the experimental class (lecture method) is 12.76% which is included in the ineffective category. The handover of nameplates and digital baby scales is expected to improve the function and role of the posyandu.